PENGARUH KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA PADA KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Fandhi ahmad (Universitas Bandar Lampung (UBL), 2017)
The issues in this research is how the employees performance in the Kecamatan Menggala Kabupaten Tulang Bawang influenced by competence and communication. This research aimed to determine the influence of competence and communication to employee performance. The hypothesis formulated is competence and communication affect the performance of employees, either partially or simultaneously. The sample used in this study amounted to 45 employees. Data collection techniques by observation, documentation and questionnaires. Research methods used by descriptive by using a quantitative analysis approach with the aid of statistical tools SPSS version 18 for the calculation of the linear regression model. The test results show that partial hypothesis competence affect the performance of employees with a contribution of 59.5%. Work Communication affects the performance of employees with a contribution of 12.6%. Simultaneous hypothesis testing showed that the competence and communication has positive and significant influence on employee performance with a contribution of 59.6%. Keywords: competence, communication, employees performance.